Contemplating on the Etiology of COVID-19 Severity and Mortality Sex Differences. (27th October 2020) - Shweiki, Dorit
COVID-19 displays a sex-biased behavior with a higher rate of intensity and mortality in men. In that sense, COVID-19 deflects-off the typical trend of many viral infections which are characterized by a higher rate of intensity and prevalence in males, yet a higher female mortality rate. Severity and mortality rates of COVID-19 are associated with several underlying diseases, which exhibit significant self-sufficient male-biased dimorphism, thus are at times hypothesized to be the ones responsible to tilt mortality balance toward higher men death in COVID-19. Yet, similar comorbidities prevail in other viral infections, raising curiosity to what makes COVID-19 unique? The answer may lay in the involvement of renin-angiotensin system and ACE2 receptor in COVID-19 progression, 2 players which are significant contributors to the fatality of COVID-19. A structured difference is evident in the expression and function of RAS and ACE2 between the sexes, presumably tipping over mortality rate tendency toward male-risk factor.